(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2009)
The micellar extraction of thallium with carboxylic acids into phases of non-ionic surfactant Triton X-100 and Triton X-114 at cloud point temperature was investigated. The optimum conditions of micellar extraction of metal ion were established. The procedure of atomic-absorption determination of thallium in the natural water after micellar extraction preconcentrating was elaborated.